For Postpartum Haemorrhage Prophylaxis between Carbetocin and Oxytocin - A Study in Tertiary Care Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Postpartum haemorrhage is a major cause of maternal deaths and ill health in low- and middle-income countries. Active management of the third stage of labour, which is generally used to reduce blood loss at birth, consists of giving the mother a drug that helps the uterus to contract, early cord clamping and controlled cord traction to deliver the placenta. Different drugs have been tried and generally either intramuscular oxytocin or intramuscular syntometrine is given. Carbetocin is an oxytocin agonist. Oxytocin agonists are a group of drugs that mimic the oxytocin action, oxytocin being the natural hormone that helps to reduce blood loss at birth. The comparison between intramuscular carbetocin and oxytocin showed carbetocin less likely to have heavy bleeding and less likely to require other medications to produce uterine contractions. The study compared carbetocin against oxytocin given in third stage of labour. Therefore, this will be rationale to carry out a study to find out the safety and effectiveness of carbetocin over oxytocin as prophylaxis of post-partum haemorrahge.Bangladesh J Obstet Gynaecol, 2023; Vol. 38(1): 5-13